Signaling crosstalk between tumor endothelial cells and immune cells in the microenvironment of solid tumors - Xu, Yuexin; Miller, Chris P.; Tykodi, Scott S.; Akilesh, Shreeram; Warren, Edus H. (Frontiers in Cell and Developmental Biology, 2024)
Tumor-associated endothelial cells (TECs) are crucial mediators of immune surveillance and immune escape in the tumor microenvironment (TME). TECs driven by angiogenic growth factors form an abnormal vasculature which deploys molecular machinery to selectively promote the function and recruitment of immunosuppressive cells while simultaneously blocking the entry and function of anti-tumor immune cells. TECs also utilize a similar set of signaling regulators to promote the metastasis of tumor cells.Meanwhile, the tumor-infiltrating immune cells further induce the TEC anergy by secreting pro-angiogenic factors and prevents further immune cell penetration into the TME.Understanding the complex interactions between TECs and immune cells will be needed to successfully treat cancer patients with combined therapy to achieve vasculature normalization while augmenting antitumor immunity. In this review, we will discuss what is known about the signaling crosstalk between TECs and tumor-infiltrating immune cells to reveal insights and strategies for therapeutic targeting.